A relação entre o Programa de Saúde da Família e o Programa Academia da Cidade de Belo Horizonte - Bruno Hudson Coutinho (2018)
Introduction: The City Academies are an important support tool in the SUS Family Health Program. Through physical activities we can combat sedentarism, obesity, chronicdegenerative diseases, providing users with a reduction in body fat, a reduction in cholesterol and triglyceride levels and an improvement in the efficiency of the cardiovascular system. The objective of this research was to study the relationship between the UBS and the City Academies regarding the routing and flow of users, from the first to the second. Methodology: The study is characterized as quantitative, through semistructured, self-administered interviews with professionals from 45 Basic Health Units of the Family Health Program of Belo Horizonte. The Statistical Package for the Social Sciences of IBM (SPSS-Softer) was used to store the data. Descriptive analysis with frequency distribution, bivariate analysis and Logistic Regression were performed. Results: A total of 1042 interviews were conducted, and 61.0% of the health servers said they referred users to practice physical activities. 17.56% said they did not forward and 21.4% answered nothing. Regarding the existence of a referral flow to the PAC, 53.7% answered to know the flow and 40.1% answered that they did not and 6.1% reported nothing. Regarding the availability of an instrument to evaluate the coronary risk for physical activity practice, type of instrument and its use, only the medical professionals (n = 69) were considered. 27.5% answered that they have instruments. 69.6% do not have instruments to evaluate. Regarding the difficulties for referral to PAC, health status, lack of interest, physical condition and disinformation were the main factors reported by the servers. The strengthening of the UBS x PAC relation was mentioned, the awareness of the users, the feed back on the referral, the training and the clarification with the ES about the Program and the monthly discussion about the PS in the NASF meetings. The first logistic regression model showed that the occupied function increases the chance of the health professional indicating the PAC to the user and their opinion that the user is uninformed decreases. The second final logistic regression model showed that the function occupied; opportunity to contribute; job satisfaction and feeling on the edge increase the chance of knowing the flow of referral to the PAC.Conclusions: The study shows that the relationship between the Family Health Program and the City Academy Program still presents gaps and needs to move forward to ensure the possibilities it opens in terms of health promotion; also shows that satisfaction with work, the work process and the job function play an important role in this relationship.